The Relationship Between Macroeconomic Variables and Employment Opportunities in Urban Areas - Muhammad Ashary Anshar; Sulkipli Sulkipli; Aminuddin Hamdat; Fauziah Fauziah (Vifada Management and Social Sciences, 2025)
Purpose: This study aims to analyze the impact of wage levels, inflation, economic growth, and investment on employment opportunities in Makassar, thereby providing an empirical understanding of the key factors influencing labor market dynamics in the region. Research Design and Methodology: This study employs a quantitative approach using multiple linear regression. Secondary data were obtained from the Central Statistics Agency (BPS) of Makassar City, covering ten years. The analysis involved a series of classical assumption tests and regression coefficient estimations to examine the effect of each independent variable on employment opportunities. Findings and Discussion: The results of the study indicate that wage levels have a significant negative effect on employment opportunities, meaning that wage increases tend to reduce labor absorption. Inflation does not have a significant effect on employment opportunities. Economic growth has been shown to have a significant positive effect, meaning that increased economic activity drives job creation. Meanwhile, the level of investment does not have a significant effect, indicating that current investment is not yet fully oriented toward labor-intensive sectors. Implications: These findings guide local governments in formulating balanced wage strategies, maintaining price stability, promoting inclusive economic growth, and directing investment toward productive sectors that expand employment opportunities.